2023
DOI: 10.3390/plants12040747
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic Effects of Polystyrene and Polymethyl Methacrylate Microplastics on Allium cepa Roots

Abstract: Plastic contamination has become one of the most pressing environmental issues due to rapidly increasing production of disposable plastic products, their fragmentation into smaller pieces, and long persistence in the environment, which affects all living organisms, including plants. In this study, Allium cepa roots were exposed to 0.01, 0.1, and 1 g L−1 of commercial polystyrene (PS-MPs) and polymethyl methacrylate microparticles (PMMA-MPs) for 72 h. Dynamic light scattering (DLS) analyses showed high stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…These studies have demonstrated that PS had a more negative effect on root growth in mung beans compared to onions. Biba et al [ 63 ] reported that there were no significant changes in onion root growth after exposure to any of the tested PS MP concentrations, compared to the control, although the highest concentration (1 g/L) caused a slight decrease in length. On the other hand, Chen et al [ 64 ] found that any applied concentration of PS MPs significantly reduced the growth characteristics of mung bean plants, including the shoot and root growth.…”
Section: Effects Of Plastics On Plant Developmentmentioning
confidence: 99%
“…These studies have demonstrated that PS had a more negative effect on root growth in mung beans compared to onions. Biba et al [ 63 ] reported that there were no significant changes in onion root growth after exposure to any of the tested PS MP concentrations, compared to the control, although the highest concentration (1 g/L) caused a slight decrease in length. On the other hand, Chen et al [ 64 ] found that any applied concentration of PS MPs significantly reduced the growth characteristics of mung bean plants, including the shoot and root growth.…”
Section: Effects Of Plastics On Plant Developmentmentioning
confidence: 99%
“…(2021b) . Nonetheless, Biba et al. (2023) observed no drastic changes in O 2 - production in onion roots under different PS MP stress levels; however, when compared with the effects of PMMA MPs, PS MP treatment showed relevantly higher O 2 - production, thereby indicating MP-type response of ROS production in the root.…”
Section: Microplastic Effects On Plant Growthmentioning
confidence: 66%
“…While some of these plastics end up in terrestrial environments, the majority find their way into aquatic ecosystems. These plastics undergo photodegradation, transforming into microplastics (classified as secondary microplastics), accumulating in the soil [ 7 ], water and sediment [ 8 ], and terrestrial and aquatic organisms [ 9 ]. Additionally, certain microplastics classified as primary microplastics are intentionally produced for various products like textiles, cosmetics, and fishing nets, entering the environment or human bodies [ 8 ].…”
Section: Introductionmentioning
confidence: 99%